Analysis of Water and Sediment Characteristics in Rongjiang River Basin - AO Liangting (Renmin Zhujiang)
The Rongjiang River Basin is a tidal reach,where the movement of water and sediment is complicated.Over the years,sediment deposition and soil erosion are serious.Hence,the study of the variations of water and sediment in the Rongjiang River Basin is of great significance for water area management and river management in the basin.Upon the comprehensive analysis of the water and sediment data of Dongqiaoyuan Hydrological Station in the mainstream of Rongjiang River from 1953 to 2017,the trend analysis of the water and sediment sequence is carried out by the moving average method and Mann-Kendall trend test.The mutation analysis is made by the Mann-Kendall mutation test and ordered cluster analysis.Meanwhile,Morlet wavelet analysis is used to discuss the periodicity of the water and sediment process.The characteristics,variations,and influencing factors of water and sediment in the Rongjiang River Basin are obtained to provide theoretical support and a digital model for further study of the characteristics of water and sediment in the basin.